CMOS high efficiency on-chip power management - Hu, John; Ismail, Mohammed; SpringerLink (Online service). (New York Springer, 2011)
This book deals with the subject matter of power management integrated circuit (IC) design, or integrated power electronics, as a response to the growing need for energy-efficient electronics. The authors introduce various power management IC design techniques to build future energy-efficient 'green' electronics. The goal is to achieve high efficiency, which is essential to meet consumers' growing need for longer battery lives.  The focus is to study topologies amiable for full on-chip implementation (few external components) in the mainstream CMOS technology, which will reduce the physical size and the manufacturing cost of the devices. Describes a number of  techniques at circuits and systems level that increase sleep-mode efficiency to prolong the battery life, without sacrificing performance parameters; Enables readers to design for compactness, which requires fewer bulky external components and circuit topologies that lend themselves easily to full on-chip integration; Offers insights on how the efficiency boosting techniques for power management IC designs work toward society's quest for higher energy efficiency.
Part I: Green Electronics and Power Management -- Green Electronics -- System Power Management -- Part II: Power Management IC Design -- Linear Regulators -- Switching Converters -- Conclusion.
Electronic reproduction.
Keywords: Low voltage integrated circuits -- Design and construction; Metal oxide semiconductors, Complementary; Electronic books